The Ethical and Spiritual Project of Martin Prozesky: Influences and Interests - Maniraj Sukdaven (Journal for the Study of Religion)
This article provides a cursory overview of the life and thought of Professor Martin Prozesky, and his contributions to academia via his ethical and spiritual project. There were many people of various personalities that influenced his life, including the path he chose in academia. Some of these were scholars, such as the internationally acclaimed Professors Alister Hardy, John Hick, Lloyd Geering, Ninian Smart, Wilfred Cantwell Smith, feminist Professors Mary Daly, Ursula King and Rosemary Radford Ruether, and various process theologians. Others were spiritual leaders such as Archbishop Desmond Tutu, Mahatma Gandhi, the Chief Rabbi of the orthodox United Hebrew Congregations of the Commonwealth (1991 – 2013), Jonathan Sacks, and the Dalai Lama.From his base in Theology and Religious Studies to his move to Ethics and Spirituality it could be established that there are five main contributions in Martin Prozesky’s work which he had made to academia and of which cognizance should be taken. These are: (1) the religious philosophy of Friedrich Schleiermacher; (2) the development of a critical theology; (3) his values-based explanation of religion; (4) the debate about God; and (5) the need for a multi-cultural, even global, multi-disciplinary approach to applied ethics with special attention to African ethics. These contributions among other works are discussed in this article. (The article was made possible through an interview with Prof. Prozesky that was recorded and transcribed.)